ANALISIS RASIO PROFITABILITAS PADA PT PRATAMA WIDYA TBK PERIODE 2023-2024 - Meidi Yanto; Friska Marlianda Sari; Novi Andriani; Tri Utami Miranty; Shandia Saqinah; Raja Amelia Agustinawati (WANARGI : Jurnal Manajemen Dan Akuntansi, 2025)
This study aims to analyze the financial performance of PT Pratama Widya Tbk through profitability ratios, including Gross Profit Margin (GPM), Operating Profit Margin (OPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) for the years 2023 and 2024. The method used is a case study with a descriptive quantitative approach based on the company’s annual financial report data. The analysis results show that in 2023, the company had a very strong financial performance across all profitability ratios. However, in 2024, there was a significant decline in ROA and ROE, although GPM and NPM remained in the “good” category. This decline indicates inefficiencies in asset utilization and decreased effectiveness in equity management. The study concludes that operational efficiency strategies and more optimal resource management are needed to improve the company’s profitability in the future. These findings provide important implications for company management in making decisions and continuously evaluating financial performance.